Rigid plastic plates at large deformations - The, Vu Van (Vietnam Journal of Mechanics, 1985)
The method developed in [8] is applied herein in order to obtain estimations of the load-deflection relationship of the hinge supported rectangular plates acted on by a uniformly distributed loading. The plate is made from rigid perfectly plastic material which yields according to the square yield condition and maximum normal yield condition. the plastic hinge line patterns shown in figs. 1. 2. are chosen. The obtained results are presented in figs. 4, 5, 6, 8.